2009
DOI: 10.12927/hcpol.2009.21189
|View full text |Cite
|
Sign up to set email alerts
|

Supply and Distribution of Primary Healthcare Registered Nurses in British Columbia

Abstract: What did we do? This study uses an existing data source to (a) describe the population and geographic distribution of registered nurses (RNs) working in primary healthcare (PHC) in British Columbia, (b) compare this workforce to PHC physicians and (c) assess the distribution of PHC-RNs relative to population health status.What did we learn? Of the 27,570 practising RNs in British Columbia in 2000, there were 3,179 (12%) in the PHC workforce. This translates into 147 people per practising RN and 1,277 people pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 7 publications
2
7
0
Order By: Relevance
“…This is consistent with the findings of other studies on the fairness of health resource distribution in specific regions [30,31]. It indicates that currently China's health administrative department allocates PHC resources according to population distribution, while ignoring geographical accessibility [32]. The results suggest that comprehensive consideration based on populational and geographical factors should be incorporated to allocate health resources rationally and scientifically.…”
Section: Discussionsupporting
confidence: 90%
“…This is consistent with the findings of other studies on the fairness of health resource distribution in specific regions [30,31]. It indicates that currently China's health administrative department allocates PHC resources according to population distribution, while ignoring geographical accessibility [32]. The results suggest that comprehensive consideration based on populational and geographical factors should be incorporated to allocate health resources rationally and scientifically.…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies show that other countries have more nurses per inhabitant than Peru and Mexico (e.g. Uruguay with nine per 10 000, the USA and Canada with 97 per 10 000; Cabrera ) and that quality of nursing care is influenced by an adequate ratio (seven nurses per 12 000 inhabitants; Cabrera , Wong ). Yet, other studies show found that Latin America and other developed countries (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…quebec has introduced delegations of medical acts and has revised its professional code. The Health Professions Act in British Columbia and the Registered Nurses Act in Nova scotia are other examples (Levesque et al 2007;Pottie et al 2008;Wong 2009). In some instances, legislation has also been enabled by collaboration between registered nurses and physicians' organizations.…”
Section: Coercive Influencesmentioning
confidence: 99%